BBC Women Reporting the World - Murrell, Colleen. author. aut Link
XV, 237 p. 12 illus., 11 illus. in color.
Keywords: This book explores the changing experiences and roles of the BBC's female journalists. Featuring original interview content, the book focuses on the careers of female foreign correspondents, from Kate Adie to Shaimaa Khalil. It begins by examining the power structures and gender-based assumptions widespread in the BBC from its inception through to the 1970s and 1980s, when international reporting opportunities first opened up for women, and then charts the changes that took place between the 1980s to the 2020s, including the recent controversy surrounding pay inequality. Featuring insights and anecdotes from the women themselves, it will appeal to a broad range of readers interested in the BBC, news journalism and gender, while also informing evolving academic debates around public service broadcasting, international news flows, media practice and issues of gender, race, class and power in the media industry. What drives women to become foreign news correspondents, do they approach their jobs differently from their male colleagues, and might their long battle for equal treatment and pay be nearing its end? These issues – and more – are handled with depth and nuance in BBC Women Reporting The World, an immensely readable work that will fascinate journalists and the public alike. Vivien Marsh, former BBC world news journalist, author of Seeking Truth in International TV News: China, CGTN and the BBC. This is a wonderful book which brings to life the extraordinary lives of many of the women foreign correspondents we take for granted on the BBC. It details the many challenges they faced from their employer and also from (men) colleagues and how they overcame them with determination. An inspiring read which I would thoroughly recommend. Emma Heywood, Senior Lecturer in Journalism Radio and Communication, Sheffield University. Colleen Murrell is Professor of Journalism at Dublin City University, Ireland. In her previous career she worked as a producer, reporter and news editor for a number of international broadcasters including the BBC, ITN, AP, TF1, CBC and ABC Australia. Murrell is the author of Foreign Correspondents and International Newsgathering: The Role of Fixers (2015) and tweets @ivorytowerjourn.